Total Hip Arthroplasty for Femoral Neck Fracture after Postoperative Intertrochanteric Fracture in a Patient with Spontaneous Fused Hip - Saori Niitsu; Shohei Okahisa; Yuki Fujihara; Yu Takeda; Shigeo Fukunishi (Case Reports in Orthopedics)
A 64-year-old woman with a spontaneous fused hip sustained a left femoral neck fracture. It was revealed that her left hip joint had a long-standing spontaneous hip fusion due to end-stage osteoarthritis. Additionally, she sustained an ipsilateral femoral intertrochanteric fracture and underwent osteosynthesis using a dynamic hip screw 8 years ago. The one-stage THA was successfully treated with no major complications and good functional recovery was obtained. The hip range of motion improved remarkably at one year after surgery. The Modified Harris Hip Score improved from an estimated 70 points before fracture to 95 points at final follow-up.